Assessing the Impacts of Infiltration and Inflow to wastewater systems - Evaluation of a Risk-based Model - Sundqvist, Joacim (My University, 2022)
Our wastewater sewer systems are aging and with additional pressure from climate change and urbanisation, there is a growing need for better management. All the water, except sanitary sewage, within a wastewater system can be referred to as water from infiltration and inflow (I/I-water). In recent years, a renewed interest in I/I-water has started to grow as it has been identified as an area with potential for improvement. Removal of I/I-water can help the overall performance of the wastewater system but better tools to study and work with I/I-water is needed. A risk-based model with the purpose to calculate the cost to society from I/I-water from a decision support perspective is developed within the PhD research project ”From hidden wastewater network to full access for smart decisions". The model calculates the cost of I/I-water from the four categories basement flooding, effects at the wastewater treatment plant (WWTP), sewer overflow (CSO/SSO), and pumping. The aim of this Master’s thesis project is to evaluate the developed model with focus on data availability, uncertainties, and how different preconditions can affect the cost of I/I-water. This was done by implementing the model on three case study areas and a reference area. Input data were mainly collected through personal communication and expert knowledge elicitation workshops. Enough data could be collected to implement the model for all three case studies, but required additional simplifications and assumptions. Basement flooding was identified as an area in need of more studies to facilitate model application and to decrease the uncertainty of the calculated cost. Restoration due to basement flooding and investment at the WWTP were shown to be the two included effects with the highest associated costs and the cost of CSO/SSO was shown to be negligible. Calculating performance indicators based on the model results were shown to have potential to contribute to valuable comparisons. Additionally, differences in cost of I/I-water between the studied areas could be identified but no general conclusions could be made as for the reasons behind the differences. Further studies including more case study areas are therefore recommended to be able to identify general patterns.
Keywords: uncertainty; cost to society; infiltration and inflow; sewer system; decision support; risk analysis